Evaluating the translation adequacy of a Filipino MMPI a reiability study - Dalupan, Mary Ann (Philippine Journal of Psychology, 1995)
This study evaluates the translation adequacy of a Filipino MMPI by employing multiple measures of instrument reliability. One hundred forty three subjects were administered both versions of the MMPI within a one-week interval utilizing a counterbalanced test-retest procedure. An adequate Filipino translation is positively indicated. Item endorsement stability was achieved where 88 percent of 566 items registered significant chi-square values (p < 0.5). Scale membership of items showed minimal translation modification warranted for 25 non-significant items. K and non K-corrected profile analyses show similarities in slope and configuration with the exception of scale Hs. Greater interversion profile similarity was noted between male mean profiles than that of females. The Filipino version likewise benefits form K-correction as a means of achieving greater profile similarity with the English K-corrected profile. High point code type consistency was achieved for two-thirds of profiles with either same high points or one scale shift among individually paired English and Filipino protocols. The relationship between MMPI scales and sex suggests a preliminary validation of the Mf scale where sex differences and role identification is achieved by both versions to a similar degree. Pending translation modification of inequivalent Filipino MMPI items, findings sufficiently reinforce the continued use of the Filipino version provided interpretations are made with consideration of the inherent limitations posed by each MMPI scale.